Modeling the effect of the wind on young trees of Pinus radiata D. Don - Cendoya Hernández, Patricio; Muñoz Sáez, Fernando (Bosque (Valdivia), 2002)
This work presents a mechanical model that allows understanding of the wind damage over juvenile plantations (under three years old) of Pinus radiata D. Don, starting from the interpretation of their dynamic behavior as affected by the wind. Based on information collected on site, the dynamic action of a windblast is characterized the same as the shape and standard dimensions of a juvenile Pinus radiata D. Don. From the differential equations of elastodynamics of changeable bodies and their solution through the employment of the numeric technique of finite elements, the mechanical behavior of an isolated tree subjected to wind blasts of known duration and magnitude is characterized. The numeric results obtained show the oscillatory nature of the movements occurring in the system (root-stem-foliage and soil) and indicate that instability will occur under the continuous action of a train of windblasts.